Post-Infectious Inflammatory Response Syndrome in an HIV-Negative Immunocompetent Elderly Patient With Cryptococcal Meningitis: A Case Report and Literature Review - Liu, Junyu; Liu, Jia; Qin, Bang-e; Yao, Shiqi; Wang, Anni; Yang, Lu; Su, Zhihui; Xu, Xiaofeng; Jiang, Ying; Peng, Fuhua (Frontiers in Immunology, 2022)
We report a previously healthy 82-year-old male with cryptococcal meningitis (CM) who represented neurological deterioration due to post-infectious inflammatory response syndrome (PIIRS) occurring in 4 months after initial anti-fungal therapy. He was treated with corticosteroids for 2 months and recovered clinically. However, the clinical manifestation, cerebrospinal fluid (CSF) and brain magnetic resonance imaging (MRI) results got worse again on the next day after corticosteroids withdrawal. The analysis of inflammatory cytokines and culture on CSF, as well as brain MRI, still suggested a diagnosis of PIIRS. Therefore, corticosteroids therapy was used again and he subsequently obtained a complete resolution of symptoms.